1962
DOI: 10.1037/h0041207
|View full text |Cite
|
Sign up to set email alerts
|

Concept-switching in middle-class, lower-class, and retarded children.

Abstract: mation about the type of test they had chosen. Subjects did not show a comparable preference for articles which emphasized the faults of the tests they had rejected. These findings have been supported by Rosen (1961) who replicated the study by Mills et al. However, Rosen also found that subjects preferred an article which advocated a change from their chosen to their nonchosen type of examination over an article which advocated the reverse type of change. It is difficult to reconcile this finding with the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
2
3

Year Published

1970
1970
1990
1990

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(33 citation statements)
references
References 18 publications
2
26
2
3
Order By: Relevance
“…The culturally deprived child tends to seek immediate rather than delayed gratification; his main concern is the &dquo;here and now,&dquo; with little consideration for future endeavors (LeShan, 1952;Lewis, 1961Lewis, , 1966Passow & Elliott, 1968;Strauss, 1962;Webster, 1966). Poverty children show higher levels of performance for concrete rewards than for the more abstract reinforcement of social praise; the opposite is evident for children of the middle class (Terrell, Durkin, & Wesley, 1959;Zigler & deLabry, 1962).…”
Section: Characteristics Of the Disadvantaged Childmentioning
confidence: 79%
“…The culturally deprived child tends to seek immediate rather than delayed gratification; his main concern is the &dquo;here and now,&dquo; with little consideration for future endeavors (LeShan, 1952;Lewis, 1961Lewis, , 1966Passow & Elliott, 1968;Strauss, 1962;Webster, 1966). Poverty children show higher levels of performance for concrete rewards than for the more abstract reinforcement of social praise; the opposite is evident for children of the middle class (Terrell, Durkin, & Wesley, 1959;Zigler & deLabry, 1962).…”
Section: Characteristics Of the Disadvantaged Childmentioning
confidence: 79%
“…Related to this argument is the work of several investigators (Davis, 1941(Davis, , 1943Terrell et al, 1959;Zigler and deLabry, 1962) indicating that lower-class children are less influenced than middle-class children by abstract, symbolic rewards. This would obviously be expected if the lower-class child were indeed developmentally younger than the middle-class child of the same chronological age.…”
Section: Social Class and The Socialization Processmentioning
confidence: 92%
“…Considerable evidence has now been presented either indicating or suggesting that middle-class children are more motivated to be correct for the sheer sake of correctness than are lower-class children (Cameron and Storm, 1965;Davis, 1964;Douvan, 1956;Ericson, 1947;Terrell, Durkin and Wiesley, 1959;Zigler and deLabry, 1962;Zigler and Kanzer, 1962). Zigler and Kanzer, for instance, found that the verbal reinforcers most effective with lower-class seven-year-olds were those indicating personal praise ("good" and "fine"), while the verbal reinforcers most effective with the middle class were those indicating their behavior was correct ("right" and "correct").…”
Section: Other Interpretations Of Intra-societal Differencesmentioning
confidence: 95%
“…With MA equated, the hierarchy was laid out as follows: for lower-class normals and institutionalized retarded (who come predominantly from the lowest socioeconomic segment), a tangible reward will be higher in the reinforcer hierarchy than will an intangible reward, while the reverse will be true for middle-class normal children. Indeed, using a conceptswitching task, Zigler and deLabry (1962) found that institutionalized retarded and noninstitutionalized lower-class children performed more effectively when there was a tangible reinforcement (a toy), while middle-class children performed more effectively with intangible reinforcement (although the difference between the middle-and lower-class groups might be considered marginal by some people, t = 1.79,/) < .05, one-tailed test).…”
Section: Probability Learningmentioning
confidence: 95%